(untitled) (Fiep Bulletin - online, 2017)
This work is part of an interdisciplinary project developed in NURBS (Center for Urban Studies) created in PPG inHumanities, Culture and Arts, UNIGRANRIO coordinated by one of the authors and composed by other authors, from the ProgramJovem Cientista do Nossos Estado / FAPERJ, a project that reflects on current issues of the Duque de Caxias city, in Rio de Janeiro,including the Museu Ciência e Vida, as an expression of monumentality that expresses and embodies a defined project for the City.Thus, we will discuss here the question of heritage within the interdisciplinary perspective, understanding how something that waschosen to be built as a fighting chance by staying in the contemporary world, where new surprises every day often leaving the bank,importance of cultural heritage is material or immaterial. To do so, choose here the Museu Ciência e Vida, as a monument to be studiednot only for its architecture but also for its activities. In this case, specifically, the exhibition where the laws of Isaac Newton movementwere shown as a way to work the scientific and physical perspectives. The exhibition "Move around! The Physics of Sports "had asproposal to unite the athletes and Newtonian physics have in common, encouraging participants to know the laws of motion Newtonand realize that these concepts are part of our daily lives, especially everyday athletes. Thus, we show how memory, heritage andscience go together in interdisciplinary perspectives in the desire for a scientific publication from a cultural perspective.